Air-gap Eccentricity Fault Diagnosis of Induction Motors Using EMD - ZHANG Lin; SUN An-quan; YANG Xin-yu; WANG Tian-yi; ZHANG Xue-li (Institute of Advanced Engineering and Science, 2013)
The accuracy of fault diagnostic systems for induction motors relies on a comparison of the currently extracted sensory features with those captured during normal operation. To detect the timing of these impacts from vibration signals accurately, this paper presented an efficiency diagnosis method based on empirical mode decomposition (EMD), aimed to diagnose the air-gap eccentricity fault of induction motors. Analyses the Hilbert modulus spectrum of stator current in induction motors by EMD, to obtain the fault characteristics frequency accurately, and distinguish the fault characteristics component from the fundamental wave in stator current. The simulation result demonstrated the high sensitivity and clarity of this proposed method, efficiently distinguish the fault frequency from the basic frequency in the stator current. DOI: http://dx.doi.org/10.11591/telkomnika.v11i7.2936